2023
DOI: 10.5194/egusphere-egu23-2667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Numerical Modeling of Heat Transfer and Thermal Attenuation Lengths in Ventilated Caves

Abstract: <p>Atmospheric temperature variations are characterized by different frequency-modes including yearly and daily fluctuations as well as yearly average temperatures. In a ventilated cave, the thermal amplitude is attenuated with increasing distance from the upper and/or lower cave entrance. Convective heat flux for dry air is exchanged with cave wall and the heat transferred by conduction to the surrounding rock is attenuated within a certain distance. Here, we aim at determining the thermal atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…All the model output files for numerical simulations (Comsol files) are available upon request from the authors and all the field data (including the three instrumented sites) can be found in https://doi.org/10.5281/zenodo.10514555 associated to Sedaghatkish et al (2024).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…All the model output files for numerical simulations (Comsol files) are available upon request from the authors and all the field data (including the three instrumented sites) can be found in https://doi.org/10.5281/zenodo.10514555 associated to Sedaghatkish et al (2024).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Text files including the numerical results plotted in Figures 4–9 are available at https://doi.org/10.5281/zenodo.10953068 cited as Sedaghatkish and Doumenc (2024). The Comsol Multiphysics file containing the data and results related to the reference case of Figures 4–6 is also available, but a license of Comsol Multiphysics software is necessary to use it.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…All the field data (including the three instrumented sites) can be found in https://doi.org/10.5281/zenodo.10514555 associated with Sedaghatkish et al. (2024).…”
Section: Data Availability Statementmentioning
confidence: 99%